Sistem Informasi Promosi Berbasis Web Pada CV. Albanesia Group - Ulandari, Tri; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2022)
Albanesia Group is a catering company that has not made full use of information and communication technology. CV. Albanesia Group does not have a website that can promote packages and menus available at CV. Albanesia Group, with the CV. Albanesia Group can make it easier in terms of the promotion of packages and menus available, which can be more known to the people of Jambi about the packages and menus available at CV. Albanesia Group. Web-Based Promotion System Design At CV. Albanesia Group uses the PHP programming language and uses object-based modeling techniques to describe system analysis and design, namely in the form of use case diagrams, class diagrams and activity diagrams. The output of this research is a prototype design of the system. Analysis and Design of a Web-Based Promotion Information System at CV. Albanesia Group. For further research, it can complement with other data management, such as Live Chat or other systems.